Effects of pinealectomy and exogenous melatonin on immunohistochemical ghrelin staining of arcuate nucleus and serum ghrelin leves in the rat - Canpolat, Sinan; Aydin, Mehmet; Yasar, Abdullah; Colakoglu, Neriman; Yimaz, Bayram; Kelestimur, Haluk (Elsevier Ireland Ltd, 2006)
Although the main source of circulating ghrelin is the stomach, it is also present in physiologically relevant amounts in the hypothalamus. It is reported that pharmacological doses of melatonin decrease blood levels of ghrelin. Thus, melatonin (MT) may be a candidate for the regulation of ghrelin synthesis in the brain. This study was therefore undertaken to investigate possible effects of pinealectomy and exogenous melatonin on hypothalamic ghrelin amount. Serum ghrelin levels following pinealectomy and administration of melatonin were also sought. Adult male Sprague-Dawley rats were divided into four groups as sham-operated (SHAM), sham-operated with melatonin treatment (SHAM-MT), pinealectomised (PNX) and melatonin-treated PNX (PNX-MT) groups. Ghrelin staining in the hypothalamus was determined by immunohistochemistry. Hypothalamic ghrelin was not observed in PNX rats. Much higher staining was detected in SHAM-MT rats compared to SHAM group. Lack of effect of melatonin on hypothalamic ghrelin in PNX rats implicates that exogenous melatonin requires an intact pineal to exert its effects. Although there were remarkable changes in the immunohistochemical activity of ghrelin in the hypothalamic arcuate nucleus, neither pinealectomy nor exogenous melatonin significantly changed serum levels of ghrelin. We have demonstrated for the first time that the pineal gland may play a role in ghrelin amount in the hypothalamus. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: arcuate nucleus; ghrelin; pinealectomy; melatonin; immunohistochemistry